Engine Torque Control of SI Engine using Linear Quadratic Integral Tracking (LQIT) Optimal Control - Triwiyatno, Aris; Nuh, Mohammad; Santoso, Ari; Sutantra, I Nyoman (IPTEK The Journal for Technology and Science, 2025)
Due to the needs of improving fuel economy and reducing emissions, it is increasingly important to achieve control over robustness behavior and meet performance objectives over the life of the vehicle. This requires the development of high performance and optimal power train controllers. The performance objectives are often conflicting, or at least interrelated. One way to potentially meet these performance requirements is to introduce a method of controlling engine torque of Spark Ignition (SI) engine using Linear Quadratic Integral Tracking (LQIT) optimal control. The goal is to develop simple algorithms which can control engine torque well, thus providing fuel control more efficient and simultaneously improving engine performance due to the needs of the driver based on throttle opening information. In this case, spark ignition engine with automatic transmission simulation model is used to meet a good performance under this controller design.